Penerapan Konseling Individual Dengan Teknik Extinction Untuk Mengatasi Egosentris Pada Remaja Di Panti Asuhan Bunda - Princess Annisa; M. Amin Sihabuddin; Zhila Jannati (Jurnal Pendidikan Sosial Dan Konseling, 2023)
This research is entitled "Application of Individual Counseling Using Extinction Techniques to Overcome Egocentricity in Adolescents in Mother's Orphanage". The aim of this research is to find out the egocentric picture before individual counseling with the extinction technique is carried out for teenagers at the Bunda Orphanage, to find out the individual counseling process to overcome egocentrism in teenagers at the Bunda Orphanage, and to find out the egocentric picture after individual counseling with the extinction technique for teenagers. at Mother's Orphanage. This research is research that uses a qualitative approach, with descriptive research methods, interview, observation and documentation data collection tools. The subjects in this research were three teenagers and one head of the mother's orphanage. The data analysis techniques used were: data reduction, data presentation, and conclusions or verification. The results of this research show that egocentrism in adolescents can be seen from the aspects of imaginary audiences, personal fables, and self-focus. The application of individual counseling with the extinction technique to overcome egocentricity in adolescents at Bunda Orphanage is the initial stage, middle stage/activity stage, and final stage, and the stage of extinction is eliminating unwanted behavior, thus enabling the counselee to adjust his/her personal behavior. better in the future, and try new things that can overcome egocentrism.